P94 Impact of in-situ simulation for the departmental induction of intensive care medicine trainees: orientate, educate, empower?. (31st December 2017) - Vincent, L; Cronshaw, H; Greig, P; Venes, T; Ellis, H; Pearse, T; Colebourn, C
Abstract : Background: Our frequently rotating trainee doctors vary significantly in background and Intensive Care Medicine (ICM) experience. Effective departmental induction is crucial to maintain patient safety standards and support trainees. We incorporated In-situ Simulation into Intensive Care Unit (ICU) departmental induction to orientate participants to the environment, meet specific Clinical Governance objectives, reinforce emergency protocols, challenge non-technical skills and foster inter-disciplinary relationships. Method: All trainee doctors rotating through ICU over 9 months participated in the simulated scenario (displaced tracheostomy and intubation) prior to their first shift. 2 senior doctors and 1 nurse delivered the training in a vacant bed space on ICU, using the Laerdal ALS mannequin. Nurses were released from patient care to participate in the scenarios. Immediate de-brief reinforced learning outcomes. Participants completed pre- and post-intervention questionnaires, incorporating objective assessment of knowledge (ICU orientation and tracheostomy guidelines) and self-report confidence scores (5-point likert scale: 1=Strongly Disagree to 5=Strongly Agree) for aspects of emergency airway management. Results: 28 trainees participated. 46% had anaesthetics as base specialty, 36% medicine, 14% single-stem ICM and 4% Emergency Medicine. 11% had no simulation experience. Post-intervention, there was increase in almost all objective measures of ICU orientation (location of drugs and airway equipment) and recall of the National Tracheostomy Safety Project tracheostomy emergency algorithm but these did not reach significance (p>0.05; Chi-Square test). There was significant improvement in all self-report confidence scores post-intervention (p<0.005; Wilcoxon Signed Rank test) (Image 1). There was marked pre-intervention inter-specialty variation in trainee confidence, with those from medical backgrounds being less confident than those from ICM or anaesthetics. 85% trainees 'agreed' or 'strongly agreed' with all subjective measures of intervention effectiveness. Discussion: The impact of this simulation training in empowering trainees is supported by trainee feedback and the significant increase in confidence scores for orientation and capabilities. The non-significant increase in objective measures of ICU orientation and knowledge, likely reflect the small sample size and 'reinforcing' nature of the scenario, rather than lack of learning per se . Imbalance between junior doctor confidence and competence can impact on patient safety, due to inappropriate risk taking, though lack of clarity in defining confidence versus competence also limits their interpretability in educational evaluation. Further work could include repeating the post-course questionnaire and scenario several weeks post-induction, to establish whether educational impact is sustained and reinforce learning outcomes. Participant performance (including non-technical skills) could be objectively assessed by the observing faculty, using validated tools. References: . Rosen MA, Hunt EA, Pronovost PJ, Federowicz MA, Weaver SJ. In situ simulation in continuing education for the health care professions: A systematic review. Journal of Continuing Education in the Health Professions 2012;32(4):243–254. . McGrath BA, Bates L, Atkinson D, Moore JA. Multi-disciplinary guidelines for the management of tracheostomy and laryngectomy airway emergencies. Anaesthesia 2012;67:1025–1041. doi:10.1111/j.1365-2044.2012.07217.x